2002
DOI: 10.1103/physreva.65.042320
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement swapping of generalized cat states and secret sharing

Abstract: We introduce generalized cat states for d-level systems and obtain concise formulas for their entanglement swapping with generalized Bell states. We then use this to provide both a generalization to the d-level case and a transparent proof of validity for an already proposed protocol of secret sharing based on entanglement swapping.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
167
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(167 citation statements)
references
References 33 publications
0
167
0
Order By: Relevance
“…Since a pioneering QSS scheme was proposed by Hillery, Bužek and Berthiaume in 1999 by using a three-particle or a four-particle entangled Greenberger-Horne-Zeilinger (GHZ) state for sharing a classical information, called HBB99 customarily for short, there has been a lot of works focused on QSS in both theoretical [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] and experimental [28,29] aspects. Almost all the existing QSS protocols can be attributed to the two types according to their goals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since a pioneering QSS scheme was proposed by Hillery, Bužek and Berthiaume in 1999 by using a three-particle or a four-particle entangled Greenberger-Horne-Zeilinger (GHZ) state for sharing a classical information, called HBB99 customarily for short, there has been a lot of works focused on QSS in both theoretical [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] and experimental [28,29] aspects. Almost all the existing QSS protocols can be attributed to the two types according to their goals.…”
mentioning
confidence: 99%
“…some users [13,14,15,16,17,18,19,20,21,22,23], and the other is used to split a secret including a classical one [13,14,15,16,17] or a quantum one [23,24,25,26,27]. Recently, Zhang, Li and Man [23] proposed a multiparty quantum secret sharing (MQSS) protocol for splitting a classical secret message among three parties, say Alice, Bob and Charlie with single photons following some ideas from the Ref.…”
mentioning
confidence: 99%
“…Gottesman showed that the size of each important share sometimes can be made half of the size of the secret if quantum states are used to share a classical secret [7]. The secret sharing protocol among n parties based on entanglement swapping of d-level cat states and Bell states was introduced by Karimipour et al [8]. Guo et al proposed a secret sharing scheme utilizing product states instead of entangled states and thus the efficiency is improved to approach 100% [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, there have been many studies on higher-dimensional QKD protocols. The QKD using four-level systems were done first [13,14], and interests soon extended to the d-dimensional case [15][16][17][18][19][20][21][22][23]. Most of these studies, however, focused on the 2-basis and the (d + 1)-basis cases, and the research on the most general case is still absent.…”
Section: Introductionmentioning
confidence: 99%